Indian federalism - Tillin, Louise (Oxford India short introductions, 2019)
To understand how politics, the economy, and public policy function in the world’s largest democracy, an appreciation of federalism is essential. Bringing to surface the complex dimensions that affect relations between India’s central government and states, this short introduction is the one-stop account to federalism in India. Paying attention to the constitutional, political, and economic factors that shape Centre–state relations, this book stimulates understanding of some of the big dilemmas facing India today. The ability of India’s central government to set the economic agenda or secure implementation of national policies throughout the country depends on the institutions and practices of federalism. Similarly, the ability of India’s states to contribute to national policy making or to define their own policy agendas that speak to local priorities all hinge on questions of federalism. Organised in four chapters, this book introduces readers to one of the key living features of Indian democracy.